Laser Writing of GaN/Ga2O3 Heterojunction Photodetector Arrays - Pengxiang Sun; Xun Yang; Kexue Li; Zhipeng Wei; Wei Fan; Shaoyi Wang; Weimin Zhou; Chongxin Shan (Advanced Materials Interfaces)
Abstract Photodetectors play a crucial role in converting light signals into electrical signals and have significant applications in various fields such as communications, imaging, and sensing. However, the fabrication of a photodetector is a complex process that involves precise control of surface preparation, lithography, and deposition techniques. Here the study demonstrates that GaN/Ga2O3 heterojunctions can be fabricated utilizing laser processing to transform the surface of GaN into Ga2O3. The GaN/Ga2O3 heterojunctions exhibit good reproducibility, uniformity, and ability to operate under zero bias, with a responsivity of 110.22 mA W−1, a detection rate of 5.56 × 1011 jones, and an external quantum efficiency of 42.34%. Moreover, an 8 × 8 photodetector array based on GaN/Ga2O3 heterojunction is fabricated via laser writing and is demonstrated to have ultraviolet imaging capabilities. This report presents the pioneering fabrication of a photodetector array using laser writing. The findings offer a versatile and scalable approach for the production of large‐area heterojunction photodetector arrays.